Antiviral Activity of Substituted Chalcones and their Respective Cu(ii), Ni(ii) and Zn(ii) Complexes - K. G. Mallikarjun (E-Journal of Chemistry)
Complexes of Cu(II), Ni(II) and Zn(II) with of 3-(phenyl)-1-(2’-hydroxynaphthyl) – 2 – propen – 1 – one (PHPO) , 3 - (4-chlorophenyl) - 1- (2’-hydroxynaphthyl)–2–propen – 1 – one (CPHPO), 3 - (4 -methoxyphenyl) -1-(2’-hydroxynapthyl)-2-propen-1-one(MPHPO),3 - (3,4-dimethoxyphenyl) –1-(2’-hydroxynaphthyl) – 2 - propen– 1 – one (DMPHPO) have been prepared and the purity of the samples were checked by elemental analysis. The ligands and their Cu(II), Ni(II) and Zn(II) complexes were tested on the infectivity of tobacco ring spot virus(TRSV) using cowpea (Vigna Sinensis) as a local lesions assay host. All the compounds were tested at different concentrations (250 ppm to 1500 ppm)on the infectivity of the virus by applying them either with virus inoculum or 24 h before of after virus inoculation to the test plants. The compounds were found to have varied effects on virus infectivity depending on compounds concentration and method of application. The statistical significance of the data was determined by using analysis of variance.